Research Progress of Therapeutic Enzymes and Their Derivatives: Based on Herbal Medicinal Products in Rheumatoid Arthritis - Cai, Ming; Ni, Wei-Jian; Han, Lan; Chen, Wei-Dong; Peng, Dai-Yin (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) acts as one of the most common, agnogenic and chronic inflammatory-autoimmune disorder which is characterized by persistent synovitis, cartilage destruction, and joint deformities, leads to a wide range of disabilities, and increased mortality, thus imposing enormous burdens. Several drugs with anti-inflammatory and immunomodulatory properties such as celecoxib, diclofenac and methotrexate are being selected as conventional drugs in the allopathic system of medicine for the treatment of RA in clinic. However, there are some serious side effects more or less when using these drugs because of their short poor bioavailability and biological half-life for a long time. These shortcomings greatly promote the exploration and application of new low- or no-toxicity drugs for treating the RA. Meanwhile, a growing number of studies demonstrate that several herbs present certain anti-inflammatory and anti-arthritic activities through different enzymes and their derivatives, which indicate that they are promising therapeutic strategies when targeting these mediators based on herbal medicinal products in RA research. This review article summarizes the roles of the main enzymes and their derivatives during the pathogenesis of RA, and clearly clarifies the explicit and potential targeted actions of herbal medicinal products that have anti-RA activity. Our review provides timely and critical reference for the scientific rationale use of herbal medicinal products, with the increasing basic research and clinical application of herbal medicinal products by patients with RA.